How to Cope With " Noise" in Social Dilemmas The Benefits of Communications (article). - Tazelaar, MIrjam J. A.
Interactions in social life may be seriously affected by negative noise, whereby actual or perceived behavior is less cooperative than was intended (e.g., arriving late due to an unforeseen traffic jam). The present research examines whether negative noise exerts detrimental effects on impression and cooperation and whether such effects could be reduced by communication. Consistent with hypotheses. Study 1 revealed that negative noise exerts detrimental effects on both impressions of partners' benign intent and cooperation and that these detrimental effects could be effectively reduced by communication about noise. Study 2 replicated both findings but only for individuals with low trust. Mediation analysis revealed that impressions of benign intent and prosocial interaction goals underlie the positive effects of communication on cooperation. -- (from the author)
Keywords: Psychology-Periodicals.